2D Inversion of magnetic and gravity data: a case study on Golgohar mine - Hamid Bizhani; Pardis Mansour Shoar; Meysam Moghadasi (International Journal of Mining and Geo-Engineering, 2023)
Because of the limitations of manipulating single geophysical data sets to interpret subsurface anomalies for many cases, it is required to combine geophysical data to decrease the ambiguity and non-uniqueness of the interpretation. Integration interpretation of two different geophysical data sets is one of the most common ways to integrate geophysical data and in this paper, we want to utilize the combination of gravity and magnetic data for the Golgohar mine in Iran. This mining case is located in the Sanandaj-Sirjan zone in the province of Kerman. Gravity and magnetic data are interpreted using a MATLAB code written based on the damped weighted minimum length solution for which the model weighting is the product of the multiplying of compactness and depth weighting constraints. At first, the inversion algorithm is applied to the synthetic case to investigate its reliability for practical application on real data. Reconstructed models from the noise-contaminated synthetic data are suggestive of the productivity of the inversion algorithm. Ultimately, the algorithm is applied for the interpretation of the real data and the inversion results of both data sets show a high correlation between the magnetite anomaly position horizontally and vertically. The results represent an anomaly with the depth ranging approximately from 25 to 130 m with the horizontal extension of about 120 m from 280 to 400 m relative to the start of the interesting profile.